Improved recovery of human islets from young donor pancreases utilizing increased protease dose to collagenase for digesting peri‐islet extracellular matrix. Issue 3 (15th October 2018) - Loganathan, Gopalakrishnan; Subhashree, Venugopal; Narayanan, Siddharth; Tweed, Benjamin; Goedde, Michael Andrew; Gunaratnam, Bakeerathan; Tucker, William W.; Goli, Praneeth; Mokshagundam, Sriprakash; McCarthy, Robert C.; Williams, Stuart K.; Hughes, Michael G.; et al.
Abstract : Human islet isolation from young donor pancreases (YDP) utilizing the current purified standard dose of collagenase‐protease enzyme mixtures often results in the release of a high percentage of mantled islets. Mantled islets are those surrounded by exocrine tissue and are difficult to purify by density gradient centrifugation, leading to poor islet recovery. Based on difference in extracellular matrix, and total collagen content between YDP and old donor pancreas (ODP, > 35 Y) led us to compare results from islet isolation using increased collagenase combination (ICC) or increased protease combination (IPC), to the standard enzyme combination (SEC) in a "trisected" pancreas model to overcome the donor‐to‐donor variability. These results showed a reduced percentage of mantled islets (17% ± 7.5%) and higher postpurification islet recovery (83.8% ± 5.6%) with IPC. Furthermore, these results were confirmed in 13 consecutive whole pancreas islet isolations utilizing IPC from VitaCyte, Roche, or SERVA collagenase‐protease enzyme mixtures. Results obtained from in vitro and in vivo islet functional assessment indicated that islets isolated using IPC retained normal islet morphology, insulin secretion, and the ability to reverse diabetes after transplantation in diabetic nude mice. This is the first report utilizing trisected pancreas to assess the effectiveness of different enzyme combinations to improve islet recovery from young donor pancreases. Abstract : This study utilizes an increased protease dose within the collagenase‐protease enzyme blend for digesting the peri‐islet extracellular matrix to improve the recovery of human islets from young donor pancreases.